2015
DOI: 10.1002/lary.25377
|View full text |Cite
|
Sign up to set email alerts
|

Nearly 3,000 salivary stones: Some clinical and epidemiologic aspects

Abstract: 4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
97
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 15 publications
(26 reference statements)
11
97
0
5
Order By: Relevance
“…Sialolithiasis accounts for about 50% of benign obstructive salivary gland diseases 1 , the annual symptomatic incidence of which has recently been estimated to be 1/10- 30,000 subjects 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Sialolithiasis accounts for about 50% of benign obstructive salivary gland diseases 1 , the annual symptomatic incidence of which has recently been estimated to be 1/10- 30,000 subjects 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1 Sialolithiasis has a reported lifetime symptomatic incidence of 1 per 10,000 to 30,000 individuals. 2 Sialolithiasis more frequently originates from the submandibular gland (76%-95%), as opposed to the parotid gland (5%-24%).…”
mentioning
confidence: 99%
“…[7,8] Evidently, a study conducted in 2015 with 2959 calculi identified, 53% of the submandibular duct calculi were in the proximal duct with an average size of 8.5 mm and most were in Lutsman [10] group II. [9] This shows that most calculi that were found in the proximal part of Wharton's duct or hilum were not at unusually large. The shape of the sialo- liths located in the duct is typically elongated as to follow the anatomy of Wharton's duct, while those situated within the gland or at the hilum tend to be spherical or oval as it was in this case.…”
Section: Discussionmentioning
confidence: 88%